ANALISIS PENGARUH DER, ROA, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM - Permata Yuardi, Putu Ayu Netta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The real estate business is known for its changing characteristics, intense competition, consistency and complexity. Rising real estate prices are driven by rising land prices and an increasing trend in land supply, often with population growth and people's growing need for housing, offices, shopping centers, amusement parks, and more. If a development company makes a big profit by raising real estate prices, it's only natural that that profit will improve business performance and raise stock prices. This study aims to obtain empirical evidence regarding the effect of DER, ROA, and firm size on stock returns. This research uses signal theory and CAPM theory. The research population is property, real estate, and building construction companies. Purposive sampling method was used as a method of determining the sample. The research sample was 215 observations. The analysis technique used is multiple linear regression analysis. The results of this study indicate that DER has a positive effect on stock returns, ROA has a positive effect on stock returns, and firm size has no effect on stock returns.